EGFR status in oral squamous cell carcinoma: comparing immunohistochemistry, FISH and CISH detection in a case series study - Bernardes, Vanessa Fátima (BMJ Publishing Group, 2013)
OBJECTIVES: To compare the immunohistochemistry (IHC) expression of epidermal growth factor receptor (EGFR) in oral squamous cell carcinomas (OSCC) with the gene amplification evaluated by fluorescence in situ hybridization (FISH) and chromogenic in situ hybridization (CISH) and their association with clinicopathological parameters. Additionally, we tested the sensibility and specificity of CISH in comparison with FISH. DESIGN: Case series study SETTING: Oral surgery and pathology department in a school of dentistry. PARTICIPANTS: 52 patients with histopathological diagnosis of OSCC. METHODS: Tumour tissue samples from 52 patients with OSCC were evaluated by IHC, FISH and CISH using tissue microarray technology. Clinicopathological data from all patients were collected. RESULTS: EGFR+ rates were 53.8% (28/52) by IHC, 5.8% (3/52) by CISH and 15.4% (8/52) by FISH. Amplification detected by CISH and FISH with IHC negative occurred in 3.8% (2/52), and one case (1.9%) showed amplification detected by CISH and FISH and protein overexpression concomitantly. There were 9.6% FISH+ cases with IHC and CISH negative rates and 6/8 (75%) FISH+ and also EGFR+ cases; however, an association between protein expression and gene amplification was not found for both techniques. IHC and FISH rates were not associated with clinicopathological features. CISH+ rates were associated with T3–T4 status. Compared with FISH assay, CISH reached a sensitivity of 37.5% and specificity of 100%. CONCLUSIONS: There is no association between EGFR expression and gene amplification in OSCC when the IHC is driven to external epitopes of the protein. Although CISH demonstrates specificity, technical problems may influence sensibility when compared with FISH.